RANCANG BANGUN SISTEM IRIGASI PEMBIBITAN PENGKONDISIAN LAHAN PADI BERBASIS ATMEGA328 DAN MONITORING JARAK JAUH DENGAN RADIO FREKUENSI 433 MHZ - Aly Nur Ariana; Zainal Abidin (Jurnal Teknika, 2018)
Â System of open-close channel or water pipe irrigation is a widely used method. Required a system that can automate the system of irrigation field so that water contribution can be done evenly and enough. As the development of an automatic field irrigation system by utilizing electrode level sensor performance, to open and close the water distribution pipe automatically with the help of ATmega328 microcontroller as the central controller system that will be embedded code-code program that is needed and can be monitored from remotely wirelessly. In this research will discuss how to make an irrigation system based on atmega328 and remote monitoring with 433 mhz radio frequency and how efficient the tool is to influence the water level sensor and soil moisture sensor so that it can work well on the system. In principle the work system of this tool starts from the first Start and then ATMega328 pin initialization reads the soil moisture sensor and water level sensor with LCD display, and sends data to RF transmitter module to send to RF receiver. Making atmega328-based irrigation system and remote monitoring with 433mhz radio frequency is made by designing tools ranging from microcontrollers, ultrasonic sensors, soil moisture sensors that can create a tool to facilitate farmer in the fields.